Validasi Metode Analisis Kolesterol dalam Telur dengan HPLC-ELSD - Hanifah Nuryani Lioe; Tika Setianingrum; Ririn Anggraeni (Jurnal Ilmu Pertanian Indonesia, 2013)
A method using high-performance liquid chomatography (HPLC) coupled with an evaporative light-scattering detector (ELSD) for the determination of cholesterol in egg was validated. A silica column and a binary mixture of hexane and isopropanol (90:10) as a mobile phase were used to separate cholesterol. Cholesterol was detected at 1.5 min using cholesterol standard and HPLC-ELSD condition: evaporation temperature 50 ºC, air pressure 2.2 bars, and flow rate of mobile phase 2 mL/min. A method linearity for the cholesterol analysis in egg as a sample matrix was obtained at a range of 50 to 3000 µg/g sample, with R2>0.990. Instrument detection limit and limit of quantitation were determined at 1.07 and 3.56 µg/mL, respectively. Recovery test results by spiking cholesterol standard in egg sample at low, medium, and high concentrations (50, 250 and 3000 µg/g ) were 122.13, 108.23, and 44.71%, respectively. Their corresponding repeatability values were 5.26, 4.29, and 10.11%. Method detection limit and intralab reproducibility (to analyze a sample) were observed at 2.30 µg/g and 0.04%. The method is valid for cholesterol analysis in egg at low and medium concentrations.